Efektivitas Aqidah sebagai Dasar Aksiomatik Pendidikan (Studi terhadap SD IT Imam Syafi’i Pekanbaru) - Nelvawita Nelvawita; M. Daffa Hanif; Khairunnas Jamal (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Education is an urgency for everyone, including children who are still in the growth stage. A good education will greatly affect future developments, especially if it provides a basis for religion and belief in the form of aqidah from an early age. So this study measures the effectiveness of aqidah as the axiomatic basis of education at the Imam Syafi'i Integrated Islamic Elementary School Pekanbaru City. This study uses a quantitative approach by referring to field data sources with the object of research being elementary school students. Then the results obtained in this study that the effectiveness of aqidah as the axiomatic basis of education in the Imam Syafi'i Integrated Islamic Elementary School in a small group with the final percentage produced, namely 94.5%, is categorized as very good. Then the presentation result in the middle group was 88.22%. While the test conducted on the broad group is with a percentage of 97.78%. All percentage results are in the range of 81% - 100%. It is concluded that teaching understanding of aqidah as the axiomatic basis of education in Imam Syafi'i Integrated Islamic Elementary School is very effective